Safety, pharmacokinetics and pharmacodynamics of TAK‐418, a novel inhibitor of the epigenetic modulator lysine‐specific demethylase 1A. Issue 12 (10th June 2021) - Yin, Wei; Arkilo, Dimitrios; Khudyakov, Polyna; Hazel, Jim; Gupta, Saurabh; Quinton, Maria S.; Lin, Jie; Hartman, Deborah S.; Bednar, Martin M.; Rosen, Laura; Wendland, Jens R.
Abstract : Aims: Dysregulation of histone methylation epigenetic marks may result in intellectual and developmental disability, as seen in Kabuki syndrome. Animal data suggest that increasing histone methylation by inhibiting lysine‐specific demethylase 1A (LSD1) may improve cognitive outcomes in a model of Kabuki syndrome. TAK‐418 is a novel LSD1 inhibitor, developed as a potential therapeutic agent for central nervous system disorders such as Kabuki syndrome. Here, we report safety, tolerability, pharmacokinetic and pharmacodynamic profiles of single and multiple doses of TAK‐418 (ClinicalTrials.gov: NCT03228433, NCT03501069). Methods: Two randomized, double‐blind, placebo‐controlled, phase 1 studies of oral TAK‐418 were performed, a first‐in‐human single‐rising‐dose (SRD) study (5–60 mg) in healthy adult male and female volunteers (placebo, n = 10; TAK‐418, n = 30), and an SRD (120–160 mg) and multiple‐rising‐dose (MRD) study (20–160 mg once daily for 10 days) in healthy female volunteers (placebo, n = 2 [SRD] and n = 6 [MRD]; TAK‐418, n = 6 [SRD] and n = 18 [MRD]). Results: TAK‐418 was well tolerated. No clinically significant changes in laboratory test results or vital signs were observed and no serious adverse events were reported. TAK‐418 had a nearly linear pharmacokinetic profile, with rapid absorption and short terminal half‐life across the evaluated dose range. No obvious accumulation was observed after daily administration for 10 days. Administration with food delayed peak plasma concentrations but overall exposure was unaffected. TAK‐418 rapidly crossed the blood–brain barrier and generally showed a dose‐dependent response in the peripheral pharmacodynamic biomarker formyl‐flavin adenine dinucleotide. Conclusion: The brain‐penetrant LSD1 inhibitor TAK‐418 was well tolerated, with pharmacokinetic and pharmacodynamic effects that support further investigation.